The Discourse of Security Language, Illiberalism and Governmentality - MacDonald, Malcolm N.; Hunter, Duncan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'This volume's innovative "postdisciplinary" approach to the critical study of security discourse will be of tremendous value to Critical Discourse Analysis and Critical Security Studies researchers. MacDonald & Hunter provide a critical analytic framework specific to security discourse which combines critical discourse, corpus linguistic, and argumentative analyses with the concepts of "governmentality," "state of exception," and "ban-opticon.' -Patricia L. Dunmire, Kent State University, USA 'MacDonald and Hunter build on recent advances in critical discourse studies, using corpus-aided methods and argumentation analysis to investigate the operation of security discourses across a range of policy fields from the London Olympics to counter-terrorism to citizenship. Not only is this a 'must read' for critical discourse analysts and political sociologists, but its accessible style and rich case studies have much to offer political practitioners themselves.' -Jane M. Mulderigg, University of Sheffield, UK This book explores how language constructs the meaning and praxis of security in the 21st century. Combining the latest critical theories in poststructuralist and political philosophy with discourse analysis techniques, it uses corpus tools to investigate four collections of documents harvested from national and international security organisations. This interdisciplinary approach provides insights into the ways in which discourse has been mobilised to construct a strategic response to major terrorist attacks and geo-political events. The authors identify the way in which it is used to realize tactics of governmentality and form security as a discipline. This at once constructs a state of exception while also adhering to the principles of liberalism. This insightful study will be of particular interest to students and scholars of subjects such as applied linguistics, political science, security studies and international relations, with additional relevance to other areas including law, criminology, sociology and economics. Malcolm N. MacDonald is Associate Professor in the Centre for Applied Linguistics at the University of Warwick, UK. His research focuses on poststructuralist discourse theory and institutional discourse, medical discourse and the discourse of security; as well as intercultural communication, intercultural ethics and postcolonial theory. Duncan Hunter is Lecturer in Applied Linguistics and TESOL at the University of Hull, UK. His current research and teaching interests are corpus linguistics, discourse analysis and ELT professional history. His most recent focus has been methods combining discourse and corpus analysis techniques. .
Chapter 1: Introduction -- Chapter 2: Locating the discourse -- Chapter 3: Postdisciplinary security discourse -- Chapter 4: Disciplinarity and discourse -- Chapter 5: Analysing security discourse -- Chapter 6: Biopolitics, governmentality, and the banopticon -- Chapter 7: Discourse of citizenship and security -- Chapter 8: Discourse of Olympic security -- Chapter 9: Discourse of nuclear proliferation -- Chapter 10: Discourse of post-9/11 US security organisations -- Chapter 11: Language, illiberalism and governmentality.
Keywords: Linguistics -- Methodology; Poststructuralism; Political science -- Philosophy; Security, International; Applied linguistics; Computational linguistics; Research Methods in Language and Linguistics; Poststructuralism; Political Philosophy; International Security Studies; Applied Linguistics; Computational Linguistics